Computer aided rheological design of extrusion dies for profiles - Carneiro, O. S. (2001)
A global methodology for the rheological design of profile extrusion dies is proposed. This methodology accounts for: (i) flow defects due to maximum admissible stresses, pressure drop and melt temperature increase; (ii) post-extrusion phenomena (shrinkage upon cooling, draw-down promoted by pulling and swelling after die exit) and (iii) flow balancing. The part of the methodology, that is concerned with flow balancing, was implemented and is here illustrated in two case studies, each one leading to the adoption of a different constructive solution. The software is based on a finite-volume method, which performs the required three-dimensional simulations, and is also briefly described.